Communication in Cournot oligopoly - Maria Goltsman; Gregory Pavlov (The University of Western Ontario, Department of Economics, 2012)
We study communication in a static Cournot duopoly model under the assumption that the firms have unverifiable private information about their costs. We show that cheap talk between the firms cannot transmit any information. However, if the firms can communicate through a third party, communication can be informative even when it is not substantiated by any commitment or costly actions. We exhibit a simple mechanism that ensures informative communication and interim Pareto dominates the uninformative equilibrium for the firms.
Keywords: C72; D21; D43; D82; D83; 330; Cournot oligopoly; communication; information; cheap talk; mediation